Perceived Self-Control Effort, Subjective Vitality, and General Affect in an Associative Structure - Bertrams, Alex (Frontiers in Psychology, 2021)
A crucial assumption of the recently developed schema model of self-control is that people’s perceived self-control efforts are related to the experience of lowered subjective vitality. In the present study, this assumption was tested. It was also examined whether perceived self-control effort is related to a diffuse affective experience (i.e., subjective vitality, general positive affect, and general negative affect as a combined factor) or is discretely related to subjective vitality, general positive affect, and general negative affect. Based on the previous literature, it was expected that the latter would better fit the data. In a survey study, university students (N = 501) completed standardized measures of their perceived self-control effort, subjective vitality, general positive affect, and general negative affect with regard to a specific frame of reference (i.e., during the current day and the last two days). Bivariate correlations and confirmatory factor analyses revealed the expected relationships, meaning that perceived self-control effort was negatively related to subjective vitality and that the statistical model with three distinct affective variables fit the data better than the model with subjective vitality, positive affect, and negative affect incorporated into one common factor. It was concluded that the findings are in line with the schema model of self-control.